Kontribusi Nilai Personal Dan Nilai Pendidikan Karakter Dalam Buku Cerita Anak Dauppare Karya Nurlina Arisnawati Untuk Siswa Sekolah Dasar - Tejo Pri Asmoro, Sri Bintang Kusumawati; Almira Durhotul Jannah; Rani Setiawaty (JANACITTA, 2023)
Abstract Indonesia is known as a country rich in literature, one of which is folklore. In the children's story book Dauppare from South Sulawesi which tells of a child who doesn't listen to his mother's words so he turns into a Baine stone. The story is written in simple language that elementary school students can easily understand. The aims of this research are (1) to describe the synopsis of the children's story book Dauppare by Nurlina Arisnawati, (2) to describe and analyze the personal value of the children's story book Dauppare by Nurlina Arisnawati, and (3) to describe and analyze the educational value of the characters in the children's story book Dauppare by Nurlina Arisnawati. This research method uses a qualitative descriptive method with the data analysis model used by researchers is Milles and Huberman data analysis. As well as the data validation technique of this research is theory and researcher triangulation. Based on the findings it was concluded that First, Dauppare's book from South Sulawesi is a traditional literary genre, because it is a form of folklore originating from Toraja Regency, West Sumatra Province. Second, the personal values ​​contained in the storybook include (1) intellectual development, (2) imagination development, (3) growth of social sense, (4) growth of ethical and religious sense, and (5) emotional development. Third, the value of character education includes (1) Religious, (2) Hard work, (3) Creative, (4) Friendly/communicative, (5) Peace-loving, (6) Social care, and (7) Responsibility.   Abstrak Indonesia dikenal sebagai negara yang kaya akan sastranya, salah satunya adalah cerita rakyat. Pada buku cerita anak Dauppare dari Sulawesi Selatan yang mengisahkan seorang anak yang tidak mendengarkan perkataan ibunya sehingga ia berubah menjadi batu Baine. Cerita tersebut dibuat dengan bahasa sederhana yang mudah dipahami oleh anak-anak siswa sekolah dasar. Tujuan   penelitian ini  (1) mendeskripsikan sinopsis buku cerita anak Dauppare karya Nurlina Arisnawati, (2) mendeskripsikan dan menganalisis nilai personal buku cerita anak  Dauppare karya Nurlina Arisnawati, dan (3) mendeskripsikan dan menganalisis nilai pendidikan karakter buku cerita anak  Dauppare karya Nurlina Arisnawati. Metode penelitian ini menggunakan metode deskriptif kualitatif dengan model analisis data yang dipakai peneliti adalah Analisis data Milles and Huberman. Serta Teknik validasi data penelitian ini adalah triangulasi teori dan peneliti. Berdasarkan hasil temuan disimpulkan bahwa Pertama, buku Dauppare dari Sulawesi Selatan bergenre sastra tradisonal, karena merupakan salah satu bentuk cerita rakyat yang berasal dari Kabupaten Toraja Provinsi Sumatra Barat. Kedua, nilai personal yang ada pada buku cerita tersebut meliputi (1) Perkembangan intelektual, (2) Perkembangan imajinasi, (3) Pertumbuhan rasa sosial, (4) Pertumbuhan rasa etis dan religuis, dan (5) Perkembangan emosional. Ketiga, nilai pendidikan karakter meliputi (1) Religius, (2) Kerja keras, (3) Kreatif, (4) Bersahabat/ komunikatif, (5) Cinta damai, (6) Peduli sosial, dan (7) Tanggung jawab.